Transhumance Herders' Perceptions Towards the Change in Temperature and Precipitation in Red Panda (Ailurus fulgens Cuvier 1825) Habitats in Jajarkot, Karnali Province, Nepal - Baral, Badri; Shrestha, Sunita; Basnet, Dipak Raj; Magar, Ganesh Bahadur; Bhandari, Parashuram; Rai, Jeevan; Bhandari, Sudeep (Journal of Environment Sciences, 2022)
The endangered red panda (Ailurus fulgens) is endemic to the Himalayas, including Jajarkot. Forest-dependent agro-pastoralists in Jajarkot rely on natural resources for their livelihoods in prime red panda habitats. This paper describes how agro-pastoralists perceive prevailing climate change threats and how they together with endangered red panda are sustaining in spite of these threats based on personal interviews, focus group discussions, key informant interviews, and observation methods. The results of the study revealed that the perceptions of the agro-pastoralists correspond with the increasing trend of temperature and the changing (both increasing and decreasing) trends of precipitation. Moreover, the agro-pastoralists have perceived the decrease in snowfall and reported the appearance of new forage and pasture species in the red panda habitat. The findings will be useful to understand the impact of climate change in the red panda range and devising adaptation strategies in these areas.